Miniaturized turbine flow sensor: design and simulation - Salami, Ifedabo Abdullahi; Abdul Malik, Noreha; Habaebi, Mohamed Hadi; Salami, Ahmed Babajide (IEEE, 2018)
This study presents the performance of a prototype miniaturised turbine flow sensor designed towards supporting home or industrial automation. The prototype was designed in SolidWork 3D CAD software and then it was 3D printed. SolidWork flow Simulation was used to simulate the effect the 3D turbine flow sensor would have on a flowing water. Water flow at 1.5m/s and 5m/s were set for the flow simulation carried out. Furthermore, a simulation was made in Matlab Simulink to validate the relationship between the voltage input and the response of the turbine flow sensor. The result of the flow simulation showed that the 3D turbine flow sensor responds to a higher flowing water velocity than to the lower water flow velocity. The Simulink simulation result also showed that the turbine flow sensor will have transient response whenever it is in contact with flowing water.